Laser‐induced Breakdown Spectroscopy of Liquid Droplets Based on Plasma‐induced Current Correlation. Issue 1 (8th November 2013) - Huang, Jer‐Shing; Lin, King‐Chuen
Abstract The main limitation for laser‐induced breakdown spectroscopy (LIBS) to analyse liquid sample remains the poor reproducibility due to shot‐to‐shot signal fluctuation. To resolve this problem, we employ electrospray scheme for liquid sample introduction and develop a correlation method based on plasma‐induced current normalization. Since the plasma‐induced current is proportional to the amount of solvent broken down by the laser pulses, it serves as an excellent reference signal for the removal of shot‐to‐shot signal fluctuation. Our current normalization method is robust and resistive to the interference of salt matrix. The limit of detection (LOD) obtained for alkali‐elements reaches sub‐milligram per litre (<1 mg/L) even with the matrix salts added up to 2000 mg/L. We also investigate the effect of laser wavelength and pulse energy on different normalization methods. We show that background normalization requires the knowledge of plasma temperature to retrieve the correlation linearity, whereas current normalization already takes into account the plasma temperature and shows linearity over wide range of laser pulse energy. With current normalization, the resultant LOD of Na sample is about 20 times better than that obtained by LIB/background normalization. In combination with a flow‐injection system for preconcentration and matrix separation, we demonstrate sensitive on‐line analysis of aluminium salt in liquid droplets. We obtained a linear dynamic range of more than two orders of magnitude and the LOD reaches 1.5 mg/L, about ten times lower than those achieved without preconcentration.